A Qualitative Study On the Doctrine of Privity to Circumvent Its Effect On Subcontractor’s Payment Claim - Yan, See Zhi; Mohd Suhaimi, Mohd-Danuri; Noorfajri, Ismail; Othman, Mohamed; Fadzida, Ismail (Malaysian Institute Of Planners, 2023)
In common law jurisdictions, the doctrine of privity has been criticised by the judiciary and academic commentators, particularly the second rule of doctrine, which states that a person who is not a party to the contract cannot sue on it to obtain promised performance, although the contract has been formed with the intention to benefit him. In certain circumstances, this rule may produce unfair and injustice result to the third party of a contract, as it prohibits the third party from enforcing the right to get benefits conferred on them. The doctrine of privity becomes relevant in the context of tendering procedures when subcontractors, who are not direct parties to the main construction contract, are involved. Hence, the aim of this paper is two-fold: to highlight the difficulties of the existing legal mechanism associated with privity rule and to suggest possible ways to circumvent the effect of the doctrine of privity on subcontractors’ payment claims in the Malaysian construction industry. By adopting the socio legal research approach, the impact of the doctrine of privity, the difficulties of the existing legal mechanisms, and the need for a possible law reform were examined. The findings were also validated by conducting semi-structured interviews with five construction law experts. Among others, the findings showed that enhancement to the existing legal mechanisms and statutory intervention can effectively circumvent the privity rule and protect the subcontractor’s right for the payment claim.